2020
DOI: 10.3389/fcell.2020.00033
|View full text |Cite
|
Sign up to set email alerts
|

Fat Wasting Is Damaging: Role of Adipose Tissue in Cancer-Associated Cachexia

Abstract: Loss of body weight, especially loss of adipose tissue and skeletal muscle weight, characterizes cancer-associated cachexia (CAC). Clinically, therapeutic options for CAC are limited due to the complicated signaling between cancer and other organs. Recent research advances show that adipose tissues play a critical role during thermogenesis, glucose homeostasis, insulin sensitivity, and lipid metabolism. Understanding the adipocyte lipolysis, the formation of beige adipocytes, and the activation of brown adipoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 98 publications
1
34
0
1
Order By: Relevance
“…Adipogenesis, the formation of adipocytes from stem cells, is important for energy homeostasis and is involved in processing triglycerol, the largest energy reserve in the body. 17 IL-1β inhibits adipogenesis as suggested by the finding that potential of adipogenic progenitor cells isolated from patients with DMD are significantly reduced when co-cultured with IL-1β-secreting macrophages. 18 We showed that anakinra normalized fat content in CKD mice (Figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenesis, the formation of adipocytes from stem cells, is important for energy homeostasis and is involved in processing triglycerol, the largest energy reserve in the body. 17 IL-1β inhibits adipogenesis as suggested by the finding that potential of adipogenic progenitor cells isolated from patients with DMD are significantly reduced when co-cultured with IL-1β-secreting macrophages. 18 We showed that anakinra normalized fat content in CKD mice (Figure 2E).…”
Section: Discussionmentioning
confidence: 99%
“…According to morphologic modifications, decreased lipid content and a proinflammatory phenotype, cachectic adipocytes are similar to TAAs (Rybinska et al, 2020). As recently demonstrated, the downregulation of adipogenic and lipogenic genes is affected early in AT, resulting in lipolysis and AT remodeling during CC (Batista et al, 2013;Sun et al, 2020). Also, CC is associated with fibrosis and inflammatory cell infiltration in SAT (Batista et al, 2016), while VAT shows a low lipolysis rate in the early stage of CC and a low de novo lipogenesis rate in later stages.…”
Section: Tumor-induced Adipose Tissue Remodelingmentioning
confidence: 86%
“…The presence of the tumor may have affected the food intake of the isolated OSCC rats that in turn showed larger tumors when compared to control rats. Furthermore, this loss of body weight may be derived from the tumor-induced cachexia [ 48 ]. Tumor-induced cachexia achieves up to 80% of the advanced-stage cancer patients, including those with head and neck cancer malignancies [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These patients exhibit significant weight loss and some of them report concerns about eating, especially when receiving palliative care [ 49 ]. Although the food consumption during carcinogenesis period was not measured in the current study, isolated rats could have lost body weight due to a lower food intake and by losing adipose tissue and skeletal muscle mass, required in the increased metabolic waste [ 48 ].…”
Section: Discussionmentioning
confidence: 99%